(untitled) (European Journal of Interdisciplinary Studies, 2017)
This paper aims to contribute to a better understanding of the structure and determinants of intra –industry trade specialization in agro food sector of Bosnia and Herzegovina over the transition period. The empirical analysis based on calculation of the following indicators: Grubel – Lloyd index (GL), Revealed Comparative Advantages (RCA indicator) and Relative unit value (RUV indicator). In order to show the level of intra-industry trade specialisation and to examine comparative advantages at sectoral level, as well for individual product group, are calculated Grubel – Lloyd index and RCA indicator. RUV indicator is used for analysis of two components of total intra-industry trade (TIIT); horizontal intra – industry trade (HIIT) and vertical intra- industry trade (VIIT) of agro-food products in Bosnia and Hercegovina. The analysis and calculations of above mentioned indicators are conducted using the data about international trade of agro-food products in Bosnia and Hercegovina for period of time 2008-2015, as well data at 4 – digit level, classified according to HS (Harmonised System). The final analysis in this paper is finished through applying K - means cluster analysis. K - means method was used for identificiation of different clusters of agricultural and food commodity groups related to comparative advantages, level of specialization in intra – industry trade, as well as the ratio between unit value export and unit value import. The emprical results indicated that GL index for observed period at sectoral level is lower than 50 percent. The values of RCA indicator for agro-food sector of Bosnia and Herzegovina in international trade and to important trade markets indicate lack of comaparative advantages. In the structure of intra – industry trade is dominated vertical specialization.